Development and acceleration of graphics processing on the Xilinx Zynq platform - Yang, Mingyu (2017)
Graphics processing has increasing demand in the field of embedded system design. Programmable SoC with software and hardware programmability provides a flexible platform for integrated embedded systems design. In this project, graphics processing algorithm is implemented on Xilinx Zynq platform. This algorithm is able to run on Linux or designed hardware system without graphics processing unit. Various acceleration and optimization methods are verified and implemented from both software and hardware approach. As a result, display speed is increased 2.3 times and processing speed is increased 6.1 times.